SUSTAINABLE TRANSPORTATION IN SOUTHEAST ASIAN COUNTRIES: IMPLEMENTATION OF GREEN TRANSPORT - Maudina, Nafrah; Purnomo, Eko Priyo (Journal of Environmental Science and Sustainable Development, 2023)
Metropolitan cities face escalating reliance on private transportation, exacerbating traffic congestion and air pollution. To address these issues, promoting eco-friendly alternatives like Mass Rapid Transit (MRT), Bus Rapid Transit (BRT), and electric vehicles is crucial. This study aims to explore the integration of green transportation to achieve Sustainable Development Goals (SDGs), utilizing bibliographical analysis with VOSviewers tools. Scopus-indexed articles (2010-2022) were scrutinized using keywords: "Green Transportation," "Manila," "Bangkok," "Jakarta," and "Sustainable Development Goals."Findings reveal the adoption of green transportation in Manila, featuring electric motorbikes, bicycles, and the transformation of private transport into e-jeepneys. Bangkok showcases electric ships for water transport and student bicycle usage, fostering an eco-conscious campus. Jakarta highlights dedicated pop bike lanes and widespread use of MRT and BRT, offering cost-effective alternatives to private transportation. These successful implementations position the cities towards achieving SDGs. This study's outcomes serve as a reference for future research, guiding endeavors to replicate successful green transportation initiatives in metropolitan settings. The hope is that these interventions will mitigate traffic congestion, air pollution, and carbon emissions in urban environments.